The Rise of Mass Consumption Societies - Matsuyama, Kiminori (Journal of Political Economy, 2002)
This paper studies mechanisms behind the rise of mass consumption societies. The development process depicted follows the Flying Geese pattern, in which a series of industries take off one after another. As productivity improves in these industries, each consumer good becomes affordable to an increasingly large number of households, which constantly expand the range of goods they consume. This in turn generates larger markets for consumer goods, which leads to further improvement in productivity. For such virtuous cycles of productivity gains and expanding markets to occur, income distribution should be neither too equal nor too unequal. With too much equality, the economy stagnates in a poverty trap. With too much inequality, the development stops prematurely.